International evaluation of research in heat-mass transfer and fluid mechanics study guide - Chobotova, V. M. (TPU Publishing House, 2024)
The study guide covers the topics necessary for writing various scientific papers. It is intended for young scientists, educators of Professional English as well as master students pursuing degrees in Heat and Power Engineering and studying Thermal Technology. It can also be used for postgraduates studying Thermal Physics, Theoretical Heat Engineering and Fluid Mechanics. The study guide holds particular significance for individuals engaged in interdisciplinary research in the fields of Fluid Physics, Aerodynamics, Combustion and Explosion Physics, Physical and Colloidal Chemistry, and Rheology.